House Prices and Bank Credit Risks — A Comparison Between China and the USA - Wu, Yu (2022)
This paper investigates the relationship between bank credit risks and house prices in China and the United States. Using vector error correction models, this paper collects data from 2000-2020 for China and the United States respectively, and models each country separately. The main results of the study can be summarized that the credit risk of Chinese banks is more influenced by real estate prices, while the credit risk of U.S. banks is less influenced by real estate prices compared to China. Different results emerged for the Granger test results in China and the United States. In addition, this paper plots the capital cycle of real estate as well as creates a real estate credit risk expression for explaining the transmission process of real estate credit risk.